MANAGEMENT OF HUMAN RESOURCE DEVELOPMENTEDUCATION IN ELEMENTRAY SCHOOL - Maharani Nimasayu Hendraswari; Siti Sutarmi Fadhilah; Peduk Rintayati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Management of human resource development in the field of education related to the role of the Principal in an effort to develop the potential that exist in educators and educational personnel. The purpose of this study is to determine the extent to which the role of Headmaster and the staff of educators and education at Kartodipuran elementary school number 21 Surakarta in an effort to explore the ability to support performance in working in the field of education. This research uses qualitative descriptive method with data collection through interview technique and documentation. The results of this study can be concluded that the principal, educators and education at Kartodipuran elementary school number 21 Surakarta has conducted various training and education activities such as job rotation, understudy, coaching and counseling, conference, outdoor training, training, simulations, lecture, self-study.